2015
DOI: 10.1007/s12598-015-0536-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduction characteristics of molybdenum trioxide with aluminum and silicon

Abstract: Thermodynamics for reduction of molybdenum oxides by aluminum and silicon were calculated, and the results show that reduction reaction is feasible at a certain temperature region. Compared to the presence of CaO or CaCO 3 , reduction products of molybdenum trioxide with aluminum and silicon at various temperatures were detected by X-ray diffraction (XRD). Results show that molybdenum trioxide is reduced by aluminum or silicon step by step, and the intermediate product is MoO 2 . At 1000°C, molybdenum trioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Furthermore, HRTEM images further revealed the presence of an AlO x interlayer at the MoO x /Al interface in the as‐deposited state (Figure a). This can be attributed to favorable thermodynamic conditions . The higher oxygen affinity of Al compared to Mo is the driving force for oxygen diffusion from MoO x toward Al resulting in the formation of AlO x interlayer as well as creation of defect states within MoO x layer.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, HRTEM images further revealed the presence of an AlO x interlayer at the MoO x /Al interface in the as‐deposited state (Figure a). This can be attributed to favorable thermodynamic conditions . The higher oxygen affinity of Al compared to Mo is the driving force for oxygen diffusion from MoO x toward Al resulting in the formation of AlO x interlayer as well as creation of defect states within MoO x layer.…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to favorable thermodynamic conditions. [23] The higher oxygen affinity of Al compared to Mo is the driving force for oxygen diffusion from MoOx towards Al resulting in the formation of AlOx interlayer as well as creation of defect states within MoOx layer. When the annealing temperature is increased to 200°C, AlOx and MoOx layers are clearly distinguishable which indicates that no major change occurs at MoOx/AlOx interface.…”
Section: Resultsmentioning
confidence: 99%
“…The weight loss in sample S2 was less than that in sample S0, which indicated that the sublimation of MoO 3 obtained from decomposition of (NH 4 ) 6 Mo 7 O 24 was not happened and may be restrained by the existence of CaO or CaCO 3 in CTPW. 32), 33) In addition, the initial temperature of weight increment (about 1000°C) that may be the starting temperature of SiC oxidation reaction in sample S2 were lower than that in sample S0. This variation showed that the MoO 3 (like alkali metal oxide or alkali earth metal oxide) could promote the formation of liquid phase in a lower temperature.…”
Section: Thermal Analysismentioning
confidence: 95%